SISTEM MUZARA'AH DAN PRAKTIKNYA DI KELURAHAN SIPATOKKONG KABUPATEN PINRANG - Nur Hayati (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2022)
This study discusses the muzara’ah system in Islamic books and its practice in the community of, Pinrang Regency. In this paper, the author limits one main problem, How is the view of Islamic economics regarding the muzara’ah system in the Pinrang Regency?. The type of research used is field research using two approaches, namely judicial and empirical. And the results of this study found the form of muzara’ah in Pinrang Regency, in cultivating the agricultural land, the people Village uses two systtems, namely 50:50 and for three , it can be said that the system they have adopted has been included in the Islamic economic system on the grounds that the system adopted is not mutually exclusive. Detrimental between the land owner and the cultivator of the agricultural land and that the muzara’ah system carried out by the people Pinrang Regency has a positive impact on the village community.